初探日治時期國民學校臺籍教師的課程意識與教學實踐之圖像：以音樂教師林妹為例 Preliminary Research in the Image of Curriculum Ideology and Instruction During Japanese Colonial Period: A Case Study of Miss Lin, a Taiwanese Music Teacher - 蔡元隆 Yuan-Long Tsai (Higher Education Foundation, 2023)
本研究旨在探討日治時期國民學校臺籍音樂教師-林妹之課程意識建構及教學實踐圖像。本研究採口述歷史方法，以訪談林妹老師的口述內容為分析文本，並輔以相關研究作為研究工具。該案例經歸納分析後得到兩個發現：一、課程意識上：其課程意識帶有反省、監控、批判與實踐的成分，例如：她透過對課程教材的察覺與質疑，催生臺灣囝仔的意識覺醒，對課程內容進行反省與批判，並透過對話反饋。上述作為亦蘊含對自我的省思調整。二、教學實踐上：其透過歌詞澄清進行轉化，將內在的實務知識轉化為與外界互動的心智思考，以及對教學行動價值的深層省思。由此可知，林妹老師的課程意識與教學實踐之圖像均以解放學生智識，使其獨立思考探究為依歸，強調智識運作及邏輯思考的自由。 This was a research of Miss Lin's, a music teacher taught in public elementary school during Japanese colonial period, construction of curricular consciousness and pedagogical praxis. The research method was oral history. By interviewing Miss Lin, the researcher analyzed texts, and with inductive method, there were two findings. Firstly, Miss Lin's construction of curricular consciousness carried some characteristics included reflection, monitoring, criticism and practice. For instance, through questioned teaching materials, she awakened Taiwanese children's curricular consciousness. The teacher and students reflected through dialogues. During the process of interactive dialogues, Miss Lin also reflected her inner self. Secondly, Miss Lin transformed some concepts by clarifying song lyrics. She not only converted inner knowledge into a more interactive teaching practice, but also had a deeper reflection about the value of teaching. To sum up, Miss Lin's image of curricular consciousness and pedagogical praxis was to set the student's mind free, to enable them to think independently and take further actions of inquiry in order to enhance their freedom of knowledge and logical thinking.